Evasão universitária, planejamento docente e singularidade discente - Fialho, Maríllia Gabriella Duarte (2020)
The present research proposed to study the university dropout from the student singularities. He considers that the phenomenon has a direct relationship with the student's life path in different stages of life and contexts. That entry into higher education, a new learning space, dynamic and diverse, challenges students to stay or leave the course, depending, among other factors, on their integration with the academic environment and with the academic proposal adopted by the teacher, emphasizing what we call teaching singularity. The search for the existence of an overlap between the teaching singularity, planning and student dropout is based on the question: How can the student singularity be considered in curriculum planning in order to minimize dropout in the face-to-face undergraduate courses on campus I at UFPB? The research question is operationalized in the objective: Identify and analyze the possibilities of relationships between university dropout and the organization of UFPB's undergraduate education plans, contemplating aspects related to the student's singularities. The thesis defended is that there is a relationship between dropout and teaching planning, due to the fact that teachers adopt ready-made plans, without considering the student singularities, their academic needs, motivations and learning difficulties. The methodology adopted, of a quali and quanti nature, was operationalized through three instruments: The first, a questionnaire with open and closed questions and applied to 660 incoming students from the periods of 2016.2, 2017.1 and 2017.2, with the intention of drawing the student profile and observe their perception, over three semesters, about the possibility of staying or evading the course. The second, a structured interview, applied to 30 students evaded from UFPB, aimed to identify the factors that contributed to the effective evasion, and finally, 70 teaching plans were raised for 14 undergraduate courses. The analysis of the information related to the question and the research objectives, as well as the thesis raised, were treated with the use of statistical methods, discourse analysis and analysis of structural, academic and relational issues specific to curriculum planning. The three instruments adopted and the analysis of their data, allowed to diagnose the phenomena that make possible the evasion and to arrive at the conclusion that there is a path taken by the student before evading; that this decision to evade occurs in stages, starting from a main cause and triggering other secondary sub-factors, such as absences of social skills, empathy, respect, ethics, civility, teamwork and communication, all of which contribute to the final decision to evade. Finally, when the teaching singularity is related to school planning, it is concluded that it is related to technical progress, focusing on the content and not on the needs and experiences of the student. It is believed that teaching planning should be balanced between technical and human progress, qualifying the student-centered teaching and learning process and making it possible to minimize university dropout. The study's approach, of an unprecedented and exploratory nature, requires further research, further reflections and deepening to strengthen the validation of the thesis.